Factor V Leiden and prothrombin G20210A mutations and risk of vaso-occlusive complications in sickle cell disease: A meta-analysis through the lens of nephrology - Lakkakula VKS Bhaskar (Society of Diabetic Nephropathy Prevention, 2019)
Introduction: Hemolysis is a fundamental feature that contributes to hypercoagulability and thrombotic complications in sickle cell disease (SCD). Factor V Leiden (FVL) and prothrombin G20210A mutations are the most common genetic thrombophilia. Objectives: The aim of this meta-analysis is to determine the relationship between FVL or prothrombin G20210A and susceptibility of vaso-occlusive complications (VOC) in SCD. Patients and Methods: For this meta-analysis, eligible studies were retrieved via two systematic searches performed on PubMed, Web of Science and Google Scholar databases. The keywords used in the former search included 'sickle cell anemia', 'SCD', 'Factor V Leiden' and 'G1691A (rs6025) mutation, the letter using the keywords 'sickle cell anemia', 'SCD', 'prothrombin, and 'G20210A (rs1799963). Results: The final number of studies included was 10 about SCD-VOC and FVL (total patients with VOC 1086 and without VOC 933), and 6 about SCD-VOC and prothrombin G20210A mutation (total patients with VOC 609 and without VOC 674). Meta-analysis in fixed effect model showed that mutant genotypes (GA+AA vs. GG) of the FVL mutation was found to be higher in SCD patients with VOC than in SCD patients without VOC (OR, 3.53; 95% CI, 2.24-5.08; P < 0.001). However, the distribution of prothrombin G20210A mutation in SCD patients with or without VOC is similar (OR, 0.900; 95% CI, 0.51-1.59; P = 0.717). Conclusion: Our meta-analysis establishes that the FVL mutation as a high-penetrant risk factor for VOC in SCD patients, whereas the prothrombin G20210A is not associated with the risk of VOC in SCD patients. To further validate the clinical utility of these prothrombotic mutations in SCD patient, large scale and prospective studies in diverse populations are warranted.